From Fixing to Possibility:Changing a learning model for undergraduate students - Pym, June (South African Journal of Higher Education, 2016)
This paper has been inspired by a journey of working mostly with first generation black students in Higher eEducation in South Africa for the past twelve years. These students have been part of a successful Academic Development (AD) programme which has managed, in recent years, to achieve a fairly dramatic increase in graduation throughput by moving from a focus on ‘fixing’ the students to a more flexible approach that engages with shifting both the institutional culture and, our teaching and learning practices, as well as, understanding what students bring to the university and their needs. Many of these students are multilingual and English is their additional language. There is a great disjuncture between student and university experiences and expectations, students they have a range of vulnerabilities and the overall class composition is both complimented by and fraught with a great array of diversity.